1996
DOI: 10.1111/j.1746-1561.1996.tb07914.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Children's Physical Activity and its Association with Adult Encouragement and Social Cognitive Variables

Abstract: Little is known about possible determinants of children's participation in physical activity. In particular, the role of adults has not been clearly identified. This study investigated contemporary social cognitive variables, in combination with likely adult influence factors, in predicting intended and self-reported vigorous physical activity for young adolescents. A questionnaire was administered to 147 boys and girls ages 13-14. Questions assessed physical activity levels, including vigorous activity, inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
98
0
20

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 18 publications
8
98
0
20
Order By: Relevance
“…Activities performed in facilities such as dance studios, recreation centers, and tennis courts are often of vigorous intensity. Others studies have found positive relationships between commercial facilities and physical activity in girls, most notably Norman et al, 24 who found that the number of private recreational facilities was associated with MVPA as measured by accelerometry in girls aged [11][12][13][14][15]. The relationship between the number of facilities and physical activity also was supported in work completed by Gordon-Larsen and colleagues, 25 although in their study the operational definition of facilities included not only commercial facilities but also schools and parks.…”
Section: Discussionmentioning
confidence: 93%
“…Activities performed in facilities such as dance studios, recreation centers, and tennis courts are often of vigorous intensity. Others studies have found positive relationships between commercial facilities and physical activity in girls, most notably Norman et al, 24 who found that the number of private recreational facilities was associated with MVPA as measured by accelerometry in girls aged [11][12][13][14][15]. The relationship between the number of facilities and physical activity also was supported in work completed by Gordon-Larsen and colleagues, 25 although in their study the operational definition of facilities included not only commercial facilities but also schools and parks.…”
Section: Discussionmentioning
confidence: 93%
“…A considerable amount of evidence suggests that parent support positively influences children’s physical activity. (5, 28, 50) An explanation for this finding may be the limitations of the parent survey used in this study, as the items in this instrument specifically refer to support provided by the parent, potentially excluding children who returned home under the supervision of a sibling or grandparent during the afterschool hours. Additionally, this survey would not account for children who spend time at the supervised home of a friend after school and the potential influence that their friend’s parent(s) may have on their physical activity habits.…”
Section: Discussionmentioning
confidence: 97%
“…La intención de seguir siendo físicamente activo en el futuro se ha mostrado como un predictor de la práctica de actividad física en diversos estudios (Biddle y Goudas, 1996;Godin, Anderson, Lambert, y Desharnais, 2005). La explicación de esta asociación se puede encontrar en la teoría de la acción planeada (Ajzen, 1991), que afirma que el determinante inmediato del comportamiento es la intención personal de realizar ese comportamiento.…”
Section: Introductionunclassified